Differential Impact of TGFB1 Variation by Metastatic Status in Androgen-Deprivation Therapy for Prostate Cancer - Shiota, Masaki; Fujimoto, Naohiro; Matsumoto, Takashi; Tsukahara, Shigehiro; Nagakawa, Shohei; Ueda, Shohei; Ushijima, Miho; Kashiwagi, Eiji; Takeuchi, Ario; Inokuchi, Junichi; Uchiumi, Takeshi; Eto, Masatoshi (Frontiers in Oncology, 2021)
Transforming growth factor-β1 (TGF-β1) plays a dual role in cancer, acting as a tumor suppressor in the early stage of cancer development and as a tumor promoter in the later stage of cancer progression in various cancers. In this study, we investigated the association between genetic polymorphisms in TGFB1 and clinicopathological characteristics or oncological outcome in prostate cancer cases treated with androgen-deprivation therapy (ADT) according to metastasis status. Japanese male patients with hormone-sensitive prostate cancer treated with ADT from 1993 to 2005 were included in this study. Genomic DNA was obtained from whole blood samples, and genotyping of TGFB1 (rs2241716 and rs4803455) was performed by PCR-based technique. No significant association between genetic polymorphisms in TGFB1 (rs2241716 and rs4803455) and clinicopathological parameters or prognosis was observed in patients with non-metastatic disease. In patients with metastatic disease, Gleason score in CT/TT carriers (rs2241716) and CA/AA carriers (rs4803455) was unfavorable compared with CC carriers. In addition, the CT/TT alleles in rs2241716 (hazard ratio, 1.82; 95% confidence interval, 1.12–2.94; P = 0.015) and the CA/AA alleles in rs4803455 (hazard ratio, 1.75; 95% confidence interval, 1.03–2.98; P = 0.040) were associated with a higher risk of progression during ADT compared with the CC allele in patients with metastatic disease. TGFB1 genetic variations were associated with adverse characteristics and progression risk in ADT among patients with metastatic disease, but not those with non-metastatic disease, supporting a distinct role of TGF-β signaling between non-metastatic and metastatic prostate cancer.